2018
DOI: 10.1111/his.13759
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological effect of PLAG1 fusion genes in pleomorphic adenoma and carcinoma ex pleomorphic adenoma with special emphasis on histological features

Abstract: Aims Pleomorphic adenoma gene 1 (PLAG1) rearrangement is well known in pleomorphic adenoma (PA), which is histologically characterised by admixed epithelial and mesenchymal components. Multiple fusion variants of PLAG1 and HMGA2 have been reported; currently, however, little is known regarding the clinicopathological impacts of these fusion types Methods and results We examined the PLAG1‐ and HMGA2‐related fusion status in 105 PAs and 11 cases of carcinoma ex PAs (CXPA) arising from salivary glands and lacrima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
(85 reference statements)
1
30
0
1
Order By: Relevance
“…Our analyses resulted in the identification of an HMGA2-WIF1 and a CTNNB1-PLAG1 fusion gene in breast PAs, and of a CRTC1-MAML2 fusion gene in a breast MEC. The HMGA2 and PLAG1 rearrangements, and the CRTC1-MAML2 fusion genes identified in the breast PAs and breast MECs of this study, have been reported in PAs and MECs arising in the salivary gland and in other anatomic locations [6][7][8]20,21,23,24 . Moreover, our findings on breast MECs are in agreement with the study by Bean et al 30 , who reported on the presence of the CRTC1-MAML2 fusion gene in two breast MECs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our analyses resulted in the identification of an HMGA2-WIF1 and a CTNNB1-PLAG1 fusion gene in breast PAs, and of a CRTC1-MAML2 fusion gene in a breast MEC. The HMGA2 and PLAG1 rearrangements, and the CRTC1-MAML2 fusion genes identified in the breast PAs and breast MECs of this study, have been reported in PAs and MECs arising in the salivary gland and in other anatomic locations [6][7][8]20,21,23,24 . Moreover, our findings on breast MECs are in agreement with the study by Bean et al 30 , who reported on the presence of the CRTC1-MAML2 fusion gene in two breast MECs.…”
Section: Discussionmentioning
confidence: 98%
“…The CTNNB1-PLAG1 fusion gene was predicted to result in a chimeric transcript encompassing exon 1 of CTNNB1 and exons 4 and 5 of PLAG1 ( Fig. 2d) and has been described in PAs of the salivary glands and of the lacrimal glands 23,24 . The CTNNB1-PLAG1 fusion identified in BPA2 was validated by fluorescence in situ hybridization (FISH) using PLAG1 dual-color break-apart probes ( Fig.…”
Section: Casesmentioning
confidence: 99%
“…[ 14 ] An extensive study of 220 PAs found that 50% had normal karyotypes, 25% had 8q12 rearrangements, and 13.2% had 12q13–15 rearrangements. [ 15 ] In 1997, Kas et al [ 1 ] reported PLAG1–CTNNB1 fusion as a critical event in the tumorigenesis of PA and CHCHD7, [ 2 ] LIFR, [ 16 ] and TCEA1 [ 2 , 4 ] as fusion partners of PLAG1 . Subsequently, HMGA2 - NFIB , [ 2 ] HMGA2 - FHIT , [ 3 ] and HMGA2 - WIF1 [ 5 ] in PAs have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent report of 105 and 11 cases of PAs and carcinoma ex PA, respectively, approximately 40% of cases harbored PLAG1 fusion genes: CTNNB1-PLAG1 in 22 cases, CHCHD7-PLAG1 in 14 cases, LIFR - PLAG1 in 4 cases, and HMGA2 fusion genes in 2 cases. [ 16 ] Hence, the PLAG1 gene is predicted to play a crucial part in the tumorigenesis of PA. Conversely, approximately half of PAs do not undergo chromosomal rearrangements. [ 17 ] In 1 compelling case of distant metastasis, Akiba et al found that both the primary PA and metastasis sites were positive for PLAG1 protein, but neither tumor harbored the PLAG1 fusion gene.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of histology, cellular atypia and stromal hyalinization have been regarded as the key delineating features of CA-ExPA from benign PA [ 36 , 38 ]. Based on immunohistochemistry (IHC), loss of expression of PLAG-1 (pleomorphic adenoma gene-1) protein and overexpression of Ki-67, p53, and HER-2 (human epidermal growth factor receptor-2) are considered suggestive of malignant transformation in otherwise benign PA [ 38 , 39 ]. At a molecular genetic level, malignant transformation of PA is further characterized by PLAG-1/HMGA-2 (High Mobility Group AT-Hook 2) fusion and rearrangement, p53 mutation, and HER-2 amplification [ 36 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%